The role of neuro‐immune interactions in cancer‐related fatigue: Biobehavioral risk factors and mechanisms - Bower, Julienne E. (Cancer, 2019)
Fatigue is a common and distressing symptom in both patients with cancer and cancer survivors. There is substantial variation in the severity and persistence of cancer‐related fatigue that may be driven by individual differences in host factors, including characteristics that predate the cancer experience as well as responses to cancer and its treatment. This review examines biobehavioral risk factors linked to fatigue and the mechanisms through which they influence fatigue across the cancer continuum, with a focus on neuro‐immune processes. Among psychosocial risk factors, childhood adversity is a strong and consistent predictor of cancer‐related fatigue; other risk factors include history of depression, catastrophizing, lack of physical activity, and sleep disturbance, with compelling preliminary evidence for loneliness and trait anxiety. Among biologic systems, initial work suggests that alterations in immune, neuroendocrine, and neural processes are associated with fatigue. The identification of key risk factors and underlying mechanisms is critical for the development and deployment of targeted interventions to reduce the burden of fatigue in the growing population of cancer survivors. Given the multidimensional nature of fatigue, interventions that influence multiple systems may be most effective. Neuro‐immune processes play a critical role in cancer‐related fatigue. In this review, biobehavioral risk factors and mechanisms for fatigue are examined with a focus on psychological, neural, neuroendocrine, and immune processes, and the implications for treatment are considered.